Huella peatonal de las ciudades medias españolas - Machín, Héctor (2015)
This paper is part of a doctoral thesis project whose aim is to do research on the pedestrian elements of 22 medium-size population cities in Spain. The study is based on the so-called “Pedestrian footprint”, a plan highlighting the pedestrian areas and green spaces. This plan can be used to have a quick, concise perception about a city’s pedestrian conditions. The methodology has mainly focused on the Internet, by using the tools and websites offered by “Google” and that make both a qualitative and quantitative difference between spatial areas, making measurements and providing different pedestrian values of the city. The Pedestrian Footprint shows general aspects about the city, such as a lack of specifically-planned structures, the existence of linear axes in coastal and riverside cities, the pedestrian imbalance and the concentration of certain types in specific areas. This study provides information about frequent pedestrian elements and shows that the historic quarters in well-established cities, the pedestrian areas in riverside or coastal cities and the new architectural models with interior pedestrian areas in new cities are the predominant typologies.